Combined Activation of Coagulation and Inflammation has an Important Role in Multiple Organ Dysfunction and Poor Outcome after Severe Trauma - Gando, Satoshi; Kameue, Takashi; Matsuda, Naoyuki; Hayakawa, Mineji; Ishitani, Toshiteru; Morimoto, Yuji; Kemmotsu, Osamu (Thrombosis and Haemostasis, 2002)
We tested the hypothesis that activated neutrophil-endothelial cell interaction in DIC can cause endothelial injury contributing to multiple organ dysfunction syndrome (MODS) and a poor outcome after trauma. Fifty-eight severe trauma patients, 29 with DIC and 29 without DIC were studied. Serial levels of soluble L-, P-, and E-selectins, ICAM-1, VCAM-1, thrombomodulin, and neutrophil elastase were measured on days 0-4 after trauma. The numbers of systemic inflammatory response syndrome (SIRS) criteria that patients met were determined, simultaneously. In the DIC patients, higher DIC scores, lower platelet counts, and a longer duration of SIRS were found compared with the non-DIC patients. The incidence of ARDS and MODS were higher in patients with DIC than in those patients without DIC, and the DIC patients had poor outcome. Soluble L-selectin (sL-selectin) level on Day 1 in the DIC patients who died was markedly lower than those in the non-DIC patients. The levels of sPand sE-selectins, sICAM-1, and sVCAM-1 were more elevated in the patients with DIC than in those without DIC on days 2 to 4. Neutrophil elastase and sThrombomodulin levels in the DIC patients persistently increased during the study period compared to those in the non-DIC patients. Maximum DIC scores in the DIC group showed good correlations with peak levels of sICAM-1, sVCAM-1, neutrophil elastase, sThrombomodulin, and the number of dysfunctioning organs. Highly activated and sustained inflammation caused by neutrophil-endothelium interaction in DIC gives rise to MODS and poor outcome in patients with severe trauma. These results suggest a close relationship between inflammation and thrombosis in posttrauma DIC.
Keywords: Trauma; disseminated intravascular coagulation (DIC); adhesion molecules; inflammation; multiple organ dysfunction syndrome (MODS)